A bibliometric review of research on digital identity: Research streams, influential works and future research paths. (January 2022) - Ante, Lennart; Fischer, Constantin; Strehle, Elias
Abstract: In recent years, potentially disruptive identity-related topics emerged, such as digital twin technology for product lifecycle management or self-sovereign identity (SSI) for sovereign data control. In this study, we identify research streams and emerging trends in academic research on digital identity through a bibliometric analysis of 1, 395 peer-reviewed articles and their 44, 412 references. We derive seven distinct research streams and their interrelations by means of co-citation analysis. We name the seven research streams: i) Digital twin technology for smart manufacturing and industrial health monitoring, ii) identity-based signcryption schemes, iii) distributed networks and user privacy, iv) user authentication in wireless sensor networks, v) attribute-based encryption schemes, vi) secure data exchange in the Internet of Things and vii) blockchain and smart contracts for secure data management . Each stream's high-impact publications and its development over time are reviewed and the interrelation between publications and streams are visualized. In addition, we extract directions for future research from the field's most influential publications. The results offer a comprehensive and systematic overview of publications and discourses in digital identity research. Highlights: We identify trends and research streams in academic research on digital identity. We derive seven distinct research streams and their interrelations. Each stream's high-impact publications and its development over time are reviewed. Directions for future research from influential publications are presented. The results offer a comprehensive overview of digital identity research.